Performance Analysis of Power Bank Fitted with Recycled Laptop Batteries (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The result of observation at Science Laboratory of State Vocational High School 3 of Surakarta shows that the power capacity of power bank fitted with recycled laptop batteries was not tested. Power bank test was conducted by preparing used laptop batteries type 18650 from its packaging for a total of five cells, selecting batteries based on their physical appearance, cleaning the pole connections, testing the voltage, testing temperature when power charging from electric outlet to power bank, testing the power drain, testing the power capacity without load, charging in the case, testing the module when power charging from electric outlet to power bank, testing the power capacity level indicator, testing power charging from power bank to recharged device, installing the power bank analyzer, and recording voltage measurement results, electric current flowing, duration of time needed to charge, and power capacity left after charging. The electric load used was a 1.2 watt LED lamp. After that, the calculation of battery power capacity was conducted, in accordance with the technical specification listed in the power, then compared to the result of test of power capacity stored in recycled power bank. Based on the result of technical specification calculation, the power bank produced had a power capacity of 50.000 watt hours. Meanwhile, in the experiment with LED lamp electric load, the power bank had a power capacity of 44.6756 watt hours. The comparison of power capacity between the technical specification and the experiment shows that the recycled power bank had performance of 89.4%. Thus, recycled power bank met the requirement of feasibility to be learning media of physics project.